2019
DOI: 10.1021/acsapm.8b00215
|View full text |Cite
|
Sign up to set email alerts
|

Low-k and Recyclable High-Performance POSS/Polyamide Composites Based on Diels–Alder Reaction

Abstract: The rapid development in electronics requires high-performance and low-k materials. Introducing additional recyclability to these materials could further promote their application from environmental and economic aspects. In this paper, we report a reversibly cross-linked composite from a newly designed maleimide functionalized POSS (mPOSS) and aromatic polyamide with pendent furan groups (POF). The Diels–Alder reaction between maleimide and furan groups allowed the facile cross-linking of POF by mPOSS, thus si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…In a totally different perspective, synthetic polymers and supramolecular assemblies can be engineered so as to provide biodegradation or, simply, chemical degradation properties, e.g., by adding reversible cross-linking bonds within the structure. Following this strategy, recyclable dielectrics were also reported, for example by Luo et al, who published, in 2019, such a dielectric [ 114 ] in the form of a reversibly cross-linked composite from a maleimide-functionalized polyhedral oligomeric silsesquioxane (POSS) and an aromatic polyamide functionalized with furan groups. The reversible Diels–Alder reaction between maleimide and furan groups allowed for the cross-linking of the two polymers to reach the best dielectric properties while in function, and subsequent efficient recycling after use ( Figure 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a totally different perspective, synthetic polymers and supramolecular assemblies can be engineered so as to provide biodegradation or, simply, chemical degradation properties, e.g., by adding reversible cross-linking bonds within the structure. Following this strategy, recyclable dielectrics were also reported, for example by Luo et al, who published, in 2019, such a dielectric [ 114 ] in the form of a reversibly cross-linked composite from a maleimide-functionalized polyhedral oligomeric silsesquioxane (POSS) and an aromatic polyamide functionalized with furan groups. The reversible Diels–Alder reaction between maleimide and furan groups allowed for the cross-linking of the two polymers to reach the best dielectric properties while in function, and subsequent efficient recycling after use ( Figure 25 ).…”
Section: Discussionmentioning
confidence: 99%
“… Synthetic route to obtain the cross-linked polyhedral oligomeric silsesquioxane (POSS) and thermal reversibility. Reproduced from [ 114 ]. Copyright 2016 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…[9,10] Therefore, most studies reported in recent years have focused on the hightemperature resistant polymeric dielectric materials with excellent heat resistance and stability of thermal movement of molecular chains. [11][12][13][14] To develop various high-temperature resistant, low dielectric constant, and low dielectric loss polymeric materials with different structures, many efforts have been done including the introduction of cross-linked network into molecular chain [15][16][17][18][19][20][21][22][23] and the promotion of thermal conductivity. [24][25][26] Fluorinated poly(aryl ether) (FPAE), as high performance polymeric material, [27,28] has been widely studied owing to their high thermal stability, excellent mechanical strength, and low dielectric constant.…”
Section: Doi: 101002/marc202000100mentioning
confidence: 99%
“…[ 9,10 ] Therefore, most studies reported in recent years have focused on the high‐temperature resistant polymeric dielectric materials with excellent heat resistance and stability of thermal movement of molecular chains. [ 11–14 ] To develop various high‐temperature resistant, low dielectric constant, and low dielectric loss polymeric materials with different structures, many efforts have been done including the introduction of cross‐linked network into molecular chain [ 15–23 ] and the promotion of thermal conductivity. [ 24–26 ]…”
Section: Figurementioning
confidence: 99%
“…The most significant branch of SQs successful application is material chemistry as nanofillers and polymers modifiers [65][66][67][68][69][70][71]. Depending on the type of applied silsesquioxane and its amount in a polymer matrix, the resulting nanocomposite material possesses improved properties, i.e., mechanical (increased elongation at break, lower friction), optical (maintained optical transparency, reduced or removed the color of the nanocomposite), thermal (increased thermal resistance and glass transition temperature, lowered thermal conductivity), and others (e.g., improved the oxidation and corrosion resistance, reduced flammability of the material) [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. There are a few possibilities to introduce silsesquioxane molecules into the polymer matrix ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%